Analisis data penelitian eksperimen model pembelajaran - Sumarlin Mus; Rusmayadi Rusmayadi (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The partner in community service is the Department of Teacher Education in the Faculty of Education at the State University of Makassar. The problem: (1) Lack of understanding of experimental research methods. (2) Lack of student knowledge in analyzing experimental research data using data analysis software, and (3) Statistics courses taught are general in nature. The target of this training is the final semester students who will be writing their thesis. The methods used are: lectures, demonstrations, discussions, and data analysis practices. The results achieved (1) the compilation of research methods and statistical curriculum tools ranging from the course syllabus to the learning plan, and (2) conducting training for students about the analysis of experimental learning model data using data analysis software (SPSS 25)